Will the Use of Contextual Indicators Make UK Higher Education Admissions Fairer? - Vikki Boliver; Stephen Gorard; Nadia Siddiqui (MDPI AG, 2015)
In the UK, as elsewhere, the use of 'contextual' data has been strongly advocated in order to inform undergraduate admissions decision-making. More than a third of UK universities currently take the socioeconomic or other background context of undergraduate applicants' attainment into account when deciding whom to shortlist, interview, make standard or reduced offers to, or accept at confirmation or clearing. Even more universities plan to do so in the future. Contextualised admissions policies are considered by many commentators to be intrinsically fairer, and to represent a potentially powerful means of addressing the persistent under-representation of HE students from less advantaged backgrounds, but their impact has not yet been rigorously evaluated. In order to be effective, the indicators must be accurate, appropriate, and complete, and policies for their use must demonstrably widen participation, presumably without compromising student achievement. This paper reviews the indicators available for judging context, and the existing evidence base on how contextually-identified students perform in higher education. It illustrates the considerable difficulties of using any available indicators, alone or in combination, in terms of trustworthiness. And it explains how their use could introduce new injustices while tackling merely the symptoms of stratified participation in HE. This is far from a counsel of despair. We need to widen participation and the use of context stills shows considerable promise. The paper therefore presents the case for a new study by the authors, looking at which of the available contextual indicators are best in practice, and what difference their use would really make to widening participation at HE.